2020
DOI: 10.2224/sbp.8594
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' transformational leadership and students' employability development: A social cognitive career perspective

Abstract: Higher education policy and talent training are failing to meet the ever-changing expectations of employers and society in Taiwan, resulting in a gap between university education and employment. We used social cognitive career theory to explore the relationships between problem-based learning, teachers' transformational leadership, and students' self-efficacy and employability. Participants were 619 undergraduates from 12 Taiwanese higher education institutions. We performed structural equation modeling and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 0 publications
3
14
3
1
Order By: Relevance
“…Lecturers who can increase self-efficacy are not only in improving personal quality, but more on self-improvement and increasing self-confidence in the abilities possessed by lecturers so that they are able to increase the achievement of lecturer performance to the maximum. This is in accordance with the statement of Suhana et al (2019), Wang et al (2020), Wu et al (2020) that the importance of self-efficacy will affect the effort required and ultimately can be seen from its performance. This study also supports the research conducted by , Rahmad et al (2021), Qureshi et al (2019) which found that self-efficacy has an effect on employee performance.…”
Section: Relationship Between Self Efficacy and Lecture Performancesupporting
confidence: 90%
See 4 more Smart Citations
“…Lecturers who can increase self-efficacy are not only in improving personal quality, but more on self-improvement and increasing self-confidence in the abilities possessed by lecturers so that they are able to increase the achievement of lecturer performance to the maximum. This is in accordance with the statement of Suhana et al (2019), Wang et al (2020), Wu et al (2020) that the importance of self-efficacy will affect the effort required and ultimately can be seen from its performance. This study also supports the research conducted by , Rahmad et al (2021), Qureshi et al (2019) which found that self-efficacy has an effect on employee performance.…”
Section: Relationship Between Self Efficacy and Lecture Performancesupporting
confidence: 90%
“…With the higher professional competence, the level of ability or skill of the lecturer will be higher, so that it will have an impact on achieving maximum lecturer performance in the teaching and learning process. This is in accordance with the statement of Wang et al (2020), Wu et al (2020) that professional competence is a pillar that will place the bureaucracy as an effective machine for the government and as a parameter of apparatus skills in achieving one's performance. Obeidat et al (2016), Praditya et al (2020) explains that competence is a rational behavior to achieve the required goals in accordance with the expected conditions.…”
Section: Relationship Between Professional Competence and Lecture Per...supporting
confidence: 90%
See 3 more Smart Citations